A Two-stages Microstrip Power Amplifier for WiMAX Applications - Amine Rachakh; Larbi El Abdellaoui; Jamal Zbitou; Ahmed Errkik; Abdelali Tajmouati; Mohamed Latrach (Universitas Ahmad Dahlan, 2018)
Amplification is one of the most basic and prevalent microwave analog circuit functions. Wherefore power amplifiers are the most important parts of electronic circuits. This is why the designing of power amplifiers is crucial in analog circuit designing. The intent of this work is to present an analysis and design of a microwave broadband power amplifier by using two stages topology. A two stages power amplifier using a distributed matching network for WiMAX applications is based on ATF-21170 (GaAs FET). The configuration aims to achieve high power gain amplifier with low return loss over a broad bandwidth. The proposed BPA is designed with a planar structure on an epoxy (FR4) substrate. The planar structure is also utilized for getting the good matching condition. The advanced design system (ADS) software is used for design, simulation, and optimization the proposed amplifier. The complete amplifier achieves an excellent power gain; is changed between 28.5 and 20dB with an output power of 12.45dBm at 1dB compression point. For the input reflection coefficient (S11) is varied between -20 and -42dB. While the output reflection coefficient (S22) is varied between -10 and - 49dB over the wide frequency band of 3.2-3.8GHz.